Postbiotic Modulation of Retinoic Acid Imprinted Mucosal-like Dendritic Cells by Probiotic Lactobacillus reuteri 17938 In Vitro - Haileselassie, Yeneneh; Navis, Marit; Vu, Nam; Qazi, Khaleda Rahman; Rethi, Bence; Sverremark-Ekström, Eva (Frontiers in Immunology, 2016)
Lactobacilli are widely used as probiotics with beneficial effects on infection-associated diarrhea, but also used in clinical trials of e.g. necrotizing enterocolitis and inflammatory bowel diseases. The possibility of using probiotic metabolic products, so called postbiotics, is desirable as it could prevent possible side effects of live bacteria in individuals with a disturbed gut epithelial barrier. Here we studied how Lactobacillus reuteri DSM 17938 cell free supernatant (L. reuteri-CFS) influenced retinoic acid (RA)-driven mucosal-like dendritic cells (DC) and their subsequent effect on T regulatory cells (Treg) in vitro. RA clearly imprinted a mucosal-like DC phenotype with higher IL10 production, increased CD103 and CD1d expression and a down-regulated mRNA expression of several inflammatory-associated genes (NFκB1, RELB and TNF). Treatment with L. reuteri-CFS further influenced the tolerogenic phenotype of RA-DC by down-regulating most genes involved in antigen uptake, antigen presentation and signal transduction as well as several chemokine receptors, while up regulating IL10 production. L. reuteri-CFS also augmented CCR7 expression on RA-DC. In co-cultures, RA-DC increased IL10 and FOXP3 expression in Treg, but pre-treatment with L. reuteri-CFS did not further influence the Treg phenotype. In conclusion, L. reuteri-CFS modulates the phenotype and function of mucosal-like DC, implicating its potential application as postbiotic.